I assume that the $Y_1$ and $Y_2$ are independent and can only take two values: $b$ or $c$. Further, I know that:

$$P(Y_1=b)=a \;\; \text{and} \;\; P(Y_1=c)=1-a$$

And similarly for $Y_2$:

$$P(Y_2=b)=a \;\; \text{and} \;\; P(Y_2=c)=1-a$$

I am being asked to produce the probability distribution of $Y_1 + Y_2$. I think that the answer will be:

$$ \begin{align} P(Y_1 + Y_2 = 2b) &= a^2 \\ P(Y_1 + Y_2 = b+c) &= a(1-a) \\ P(Y_1 + Y_2 = 2c) &= (1-a)^2 \end{align} $$

But it's just something that I believe would make sense. I have no good explanation for that result. My question is whether this result is correct and if so, could someone try to explain that to me or at least point me in the right direction?

  • 1
    $\begingroup$ If $Y_1$ takes a value of $b$ and $Y_2$ takes a value of $c$, what would it mean for $Y_1 + Y_2$ to take a value of $b+c$? $\endgroup$
    – Dave
    Apr 19, 2021 at 17:07

1 Answer 1


It’s correct except the second because it’s either $Y_1=b, Y_2=c$ or $Y_1=c, Y_2=b$. That makes $2a(1-a)$.

Your intution is correct, you’ll write the cases that lead to a specific outcome and accumulate the probabilities. Here, $$P(Y_1=b, Y_2=c)=P(Y_1=b)P(Y_2=c)=a(1-a)$$

A quick check: If you sum all three probabilies, it makes 1.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.